LEGAL ANALYSIS OF ABORTION CRIME PERFORMED BY UNDERAGE OF RAPE VICTIMS IN THE PERSPECTIVE OF LEGAL DEVELOPMENT - Fitri Nuraini; Abdul Haris Semendawai; Slamet Riyanto (Jurnal Hukum Jurisdictie, 2023)
Criminal acts are currently a major concern, both from the top, namely the government and from the general public. The number of abortions in Indonesia is currently quite high, no less than two million cases per year. Until now there have been many different responses to abortion, religious experts, health experts, economists have given statements, each of which is against or even supports, religious experts view that whatever the reason abortion is an act that is contrary to religion because it kills the life of the fetus which means committing murder. Sexual violence that generally occurs is violence in the public domain, such as rape, sexual abuse, sexual harassment, and so on. The rape crime case causes the most difficulties in settlement both at the stages of investigation, prosecution, and at the stage of imposing a decision, in addition to the difficulties within the limits above, as well as difficulties in proving it becauserape or sexual immorality is generally carried out without the presence of other people. The rise of the crime of rape has become a special concern for feminists and also the wider community. This concern arises because apart from looking at upholding justice by punishing the perpetrators, it is also necessary to regulate rape victims, especially for victims who are pregnant with the children of the perpetrators of rape. Considering the possibility that the victim of rape could have a child as a result of the rape, this can bring future suffering to the victim. In practice, the problem regarding the effectiveness of the law on abortion, especially for rape victims, still raises pros and cons. Being a victim of rape alone is hard enough, especially when coupled with the occurrence of pregnancy as a result of rape. Abortion is not only a medical or health problem, but also a social problem related to the notion of freedom that a society adheres to. Meanwhile, according to Indonesian law, abortion is seen as a criminal act, because abortion is a real phenomenon, although more cases are covered up than reported. The act of abortion is also an act of dilemma, because not least of the existing practices are actually many mothers who have lost their lives due to having abortions.